2003
DOI: 10.1002/ajmg.a.20496
|View full text |Cite
|
Sign up to set email alerts
|

GTF2I hemizygosity implicated in mental retardation in Williams syndrome: Genotype–phenotype analysis of five families with deletions in the Williams syndrome region

Abstract: Most individuals with Williams syndrome (WS) have a 1.6 Mb deletion in chromosome 7q11.23 that encompasses the elastin (ELN) gene, while most families with autosomal dominant supravalvar aortic stenosis (SVAS) have point mutations in ELN. The overlap of the clinical phenotypes of the two conditions (cardiovascular disease and connective tissue abnormalities such as hernias) is due to the effect of haploinsufficiency of ELN. SVAS families often have affected individuals with some WS facial features, most common… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
136
0
6

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(145 citation statements)
references
References 54 publications
(72 reference statements)
3
136
0
6
Order By: Relevance
“…However, the location of the breakpoints in nonhomologous or with low similarity sequences suggests that the most likely mechanism leading to this atypical rearrangements may be nonhomologous end joining or other processes that do not required high homology at the breakpoint, and support the proposal that other mechanisms predisposes to genomic instability of the WBS region 31 This study underscores the importance to map precisely the WBS deletion boundaries to revaluate the significance of the WBS genes hemizygosity in the pathogenesis of epilepsy, facial features, and neurological phenotypes. [32][33][34][35][36][37][38][39][40] CONFLICT OF INTEREST All patients and/or their parents gave written consent for the study, for genetic testing some gave consent for publication of photos. Ethics Committee approval was not required as this was not a specific study but a report of clinical investigation undertaken for four WBS patients, as part of their standard clinical care.…”
Section: Patient Wbs166mentioning
confidence: 99%
“…However, the location of the breakpoints in nonhomologous or with low similarity sequences suggests that the most likely mechanism leading to this atypical rearrangements may be nonhomologous end joining or other processes that do not required high homology at the breakpoint, and support the proposal that other mechanisms predisposes to genomic instability of the WBS region 31 This study underscores the importance to map precisely the WBS deletion boundaries to revaluate the significance of the WBS genes hemizygosity in the pathogenesis of epilepsy, facial features, and neurological phenotypes. [32][33][34][35][36][37][38][39][40] CONFLICT OF INTEREST All patients and/or their parents gave written consent for the study, for genetic testing some gave consent for publication of photos. Ethics Committee approval was not required as this was not a specific study but a report of clinical investigation undertaken for four WBS patients, as part of their standard clinical care.…”
Section: Patient Wbs166mentioning
confidence: 99%
“…It has been shown that GTF2I interacts with GTF2IRD1 [131]. Studies on phenotypic features in patients with partial deletions of WBS region suggest that GTF2I and GTF2IRD1 have overlapping function and are involved in the development of the cognitive-behavioural profile of WBS, especially the severe visuospatial construction deficit and the hypersociability [92,93,132]. Immunhistological staining on brain tissues from WBS patients revealed a lack of staining for GTF2I in neurons from the posterior parietal lobe which include parts of the dorsal parietal visual pathway [133].…”
Section: Genomic Region Of Block Bmentioning
confidence: 99%
“…The detection of a normal full-scale IQ in our patient supports the previous assumptions that GTF2IRD1 and GTF2I genes are crucial for WBS cognitive features. 19,22,[27][28][29][30][31] Nevertheless, we have to emphasize that our patient exhibits a peculiar discrepancy between verbal IQ and performance IQ, resembling the PIQ/VIQ ratio that has been reported in typical WBS patients. 19,32,33 This finding seems contrary to previous reports of absent or minor visuospatial deficit in atypical WBS patients keeping GTF2IRD1 and GTF2I genes.…”
Section: Discussionmentioning
confidence: 67%
“…From these studies, it has been argued, for example, that CLIP2 hemizygosity contributes to motor coordination abnormalities. 27 Other reports suggested that the GTF2I and GTF2IRD1 genes have dosagedependent influences on craniofacial and neurological development and that hemizygosity for these genes appears to be associated with the general intellectual disability/mental retardation 22 and/or visuospatial construction difficulties. 19,21,24,[28][29][30] Finally, further insights into genotype-phenotype correlations come from an intriguing report of an individual without the abnormal motor behavior and the specific spatial and impaired visual-spatial capacities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation